1999
DOI: 10.1046/j.1365-2168.1999.00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for locally recurrent breast cancer in patients previously treated with conservative surgery

Abstract: Since the type of surgery did not seem to affect survival, breast conservation can be considered in selected patients with IBTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
1
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(85 citation statements)
references
References 16 publications
2
72
1
9
Order By: Relevance
“…6 This was not a randomized study; at a median follow-up of 73 months after the second surgery, the overall survival rate at 5 years was 70% in the 134 patients who had undergone a mastectomy compared with 85% of patients who underwent local excision. No difference was noted with regard to the disease-free survival between patients who underwent a mastectomy and those who underwent local reexcision.…”
Section: Patient Outcomes After Conservative Surgery Alone For Inbreamentioning
confidence: 97%
See 3 more Smart Citations
“…6 This was not a randomized study; at a median follow-up of 73 months after the second surgery, the overall survival rate at 5 years was 70% in the 134 patients who had undergone a mastectomy compared with 85% of patients who underwent local excision. No difference was noted with regard to the disease-free survival between patients who underwent a mastectomy and those who underwent local reexcision.…”
Section: Patient Outcomes After Conservative Surgery Alone For Inbreamentioning
confidence: 97%
“…A similarly low rate of chest wall recurrence (4%) was reported by Salvadori et al and also may be the result of the inclusion of patients with initial Stage I and Stage II disease. 6 Huang et al 11 found that the rate of local recurrence after mastectomy was significantly higher in patients with a true local recurrence at the site of the initial breast-conserving surgery compared with patients with recurrent tumors detected elsewhere in the breast (18% vs. 2%).…”
Section: Local Recurrence Risk After Mastectomy For In-breast Local Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Local radical resection alone can only be offered to one-third of the patients with recurrence [19,20], and they achieved a 5-year diseasefree survival rate of 45.5% [21]. Although local radical surgery is usually recommended, this may not be feasible in sizeable tumors [22]. Chemotherapy for LRBC has also been explored, but it was not found to be very effective [21].…”
Section: Discussionmentioning
confidence: 99%